Socio-demographic and clinical variables affecting quality of life in maxillectomy patients rehabilitated with obturator prostheses - Deepa Deka (Bioinformation, 2026)
Despite the continued use of obturator prostheses for maxillectomy rehabilitation, evidence on how socio-demographic and clinical factors influence early quality of life and prosthesis function, particularly in the North-East Indian population, remains limited. Therefore, it is of interest to evaluate the influence of socio-demographic and clinical factors on early quality of life and obturator function among 45 maxillectomy patients rehabilitated with interim obturator prostheses. Urban residence, Aramany defect class, remaining maxillary teeth, radiotherapy status and defect etiology showed significant associations with quality of life (p